SEARCH FOR LONG-TERM VARIATIONS OF dKe-dMe STARS - Bondar’, N. I. (Одеські астрономічні публікації, 2017)
Measurements of brightness of 29 red dwarf stars and 3 stars of other types were made on time scales of 5 - 90 years using plates archives of Sternberg State Astronomical Institute (Moscow), Astronomical Observatory of Odessa State University and Sonneberg Observatory (Germany). The sensitivity of plates are close to B band. The long- term changes in yearly mean magnitude have been detected or suspected for 10 dKe-dMe objects. Two stars, V833 Tau and PZ Mon, show high amplitude of variability up to 0.6 - 1.0 mag. The range of variability in mean light of the other eight stars is of 0.2 - 0.5 mag. The light curves show typical times of long-term variability of about 30-60 years. Changes of the mean light of the remained dKe-dMe stars and three other stars of other types - FK Com, V654 Her, AE Aqr - do not exceed 0.2 mag. Complete paper is to be published in: Izvestija Krymskoy Astrofizicheskoy Observatorii, v.91.